The relationship between chemokines CCL2, CCL3, and CCL4 with the tumor microenvironment and tumor-associated macrophage markers in colorectal cancer. Issue 11 (November 2018) - De la Fuente López, Marjorie; Landskron, Glauben; Parada, Daniela; Dubois-Camacho, Karen; Simian, Daniela; Martinez, Maripaz; Romero, Diego; Roa, Juan Carlos; Chahuán, Isidora; Gutiérrez, Rocío; Lopez-K, Francisco; Alvarez, Karin; et al.
A complex network of chemokines can influence cancer progression with the recruitment and activation of hematopoietic cells, including macrophages to the supporting tumor stroma promoting carcinogenesis and metastasis. The aim of this study was to investigate the relation between tissue and plasma chemokine levels involved in macrophage recruitment with tumor-associated macrophage profile markers and clinicopathological features such as tumor–node–metastases stage, desmoplasia, tumor necrosis factor-α, and vascular endothelial growth factor plasma content. Plasma and tumor/healthy mucosa were obtained from Chilean patients undergoing colon cancer surgery. Chemokines were evaluated from tissue lysates (CCL2, CCL3, CCL4, CCL5, and CX3CL1) by Luminex. Statistical analysis was performed using Wilcoxon match-paired test ( p   <  0.05). Macrophage markers (CD68, CD163, and iNOS) were evaluated by immunohistochemistry samples derived from colorectal cancer patients. Correlation analysis between chemokines and macrophage markers and clinicopathological features were performed using Spearman's test. Plasmatic levels of chemokines and inflammatory mediators' vascular endothelial growth factor and tumor necrosis factor-α were evaluated by Luminex. Tumor levels of CCL2 (mean ± standard deviation = 530.1 ± 613.9 pg/mg), CCL3 (102.7 ± 106.0 pg/mg), and CCL4 (64.98 ± 48.09 pg/mg) were higher than those found in healthy tissue (182.1 ± 116.5, 26.79 ± 22.40, and 27.06 ± 23.69 pg/mg, respectively p  < 0.05). The tumor characterization allowed us to identify a positive correlation between CCL4 and the pro-tumor macrophages marker CD163 ( p   =  0.0443), and a negative correlation of iNOS with desmoplastic reaction ( p   =  0.0467). Moreover, we identified that tumors with immature desmoplasia have a higher CD163 density compared to those with a mature/intermediated stromal tissue ( p   =  0.0288). Plasmatic CCL4 has shown a positive correlation with inflammatory mediators (tumor necrosis factor-α and vascular endothelial growth factor) that have previously been associated with poor prognosis in patients. In conclusion High expression of CCL4 in colon cancer could induce the infiltration of tumor-associated macrophages and specifically a pro-tumor macrophage profile (CD163 + cells). Moreover, plasmatic chemokines could be considered inflammatory mediators associated to CRC progression as well as tumor necrosis factor-α and vascular endothelial growth factor. These data reinforce the idea of chemokines as potential therapeutic targets or biomarker in CRC.